Are solo driving commuters ready to switch to carpool? Heterogeneity of preferences in Lyon's urban area. (January 2022) - Le Goff, Alix; Monchambert, Guillaume; Raux, Charles
Abstract: We conduct a discrete choice experiment on 1556 solo-driving commuters in Lyon, France to estimate the values of end-to-end travel time (VoTT) of commuting trips in the presence of a HOV-lane for four modes: Solo Driver, Carpool Driver, Carpool Passenger and Public Transport. Using discrete choice models, we find a strong heterogeneity in VoTT across modes and individuals. The analysis of individual heterogeneity distinguishes four behavior patterns: reluctant to mode change (20% of our sample), preferring the three alternative modes over solo driver (35%), preferring public transport (12%) and preferring driver modes whether solo or carpool (32%). We find that current solo drivers are more likely to switch to carpooling as a driver rather than as a passenger. As suggested by our simulations aimed at marginally changing mode shares, carpool passenger will be the scarce resource if one wants to decrease car traffic by stimulating carpooling for commuting trips. Highlights: Compared commuting values of time for solo driver, public transport, and carpool as a passenger and as a driver. Found large heterogeneity in preferences across solo drivers. Preferences are linked with attitude statements and we provided a solo-driver's typology. Finding carpool drivers will be easier than carpool passengers among current solo drivers.